Heavy metal assessment of polluted soil around Hatirjheel Lake of Dhaka city, Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2017)
Heavy metals contamination in soil is a big issue to the environment because of its potential risk to the ecosystem and human health. Industrialization increases the disposal of industrial wastes containing heavy metals. Most industries are located near the bank of rivers or Lakes where industries can dump their effluents without proper treatment. In this study, an investigation was carried out to evaluate the heavy metals of the contaminated soil near HatirjheelLake of Dhaka city, Bangladesh. The collected soil samples were air-dried, acid digested and aliquots were analyzed by the atomic absorption spectroscopy for the quantification of heavy metals. The ranges of heavy metals were found in soil: arsenic 2.733.3 mg/kg, lead 9.574.9 mg/kg, chromium 21.843.1 mg/kg, manganese 138.3222.7 mg/kg and iron 159032.9246382.8 mg/kg, respectively. Cadmium was below the detection limit. The dominance of heavy metals series in the soil follows: Fe >Mn> Cr >Pb> As > Cd. Heavy metals content in the soil by comparison with the USEPA guidelines show that Pb was non-polluted; Cr and Mn were moderately polluted; As and Fe were heavily polluted in the study area. Heavy metals accumulation in the soil could pose a potential risk to the ecosystem as well as to human health.Bangladesh J. Sci. Ind. Res. 52(1), 61-66, 2017